Characteristics of patients who are acutely admitted to hospital under surgical care and do not have a surgical procedure – Is there an alternative to admission?. Issue 5 (October 2017) - Ryan, Michael; Kelliher, Gerry; Mealy, Ken; Keane, Frank
Abstract: Introduction: Previous work has shown that 56% of all acute surgical admissions in Ireland in 2012 did not have a formal surgical procedure. In light of the pressures on health systems internationally and the lack of relevant data on this topic in the literature, we examined the characteristics of this cohort of patients in Ireland. Methods: Discharge data on acutely admitted patients who did not undergo a surgical procedure was extracted from the Hospital Inpatient Enquiry (HIPE) database for the year 2013. These were analysed by age, sex, diagnoses, procedures performed and length of stay in hospital. Results: In 2013, 63, 079 patients were admitted acutely under surgical care and then discharged without undergoing a formal surgical procedure compared to 49, 903 who had a surgical procedure. Most of the discharges not having formal surgery were treated by general surgical specialities ( n  = 41, 434) and the average length of stay was 4.8 days. Approximately half of these patients ( n  = 32, 194) did not have any HIPE coded procedure, surgical or otherwise, during their admission into hospital. Conclusions: A considerable number of patients were admitted to Irish surgical units in 2013 and were discharged again without any formal surgical intervention. We postulate that some of these patients may not require admission to hospital and outline mechanisms which may prevent admissions Such mechanisms could allow for greater capacity for scheduled patients in currently overstrained surgical units.